Tornar-se professor formador pela experiência formadora: vivências e escritas de si - Carrilho, Maria de Fátima Pinheiro (2007)
This thesis describes and analyzes the trajectory of education of an educator-teacher group to become tutor of memorials (final work of the course Normal Superior in Instituto de Educação superior President Kennedy IFESP-Natal-RN). The writing of memorials (self-biographical writing) propitiates to the pupil that writes a reflection on his/her student and professional life, and to whom guides an evolution in his/her professional education. From the methodological point of view, we adopt an etnomethodological perspective of qualitative approach which describes the reality of real citizens inserted in a real situation of education. It is constituted of participants of the research of 32 educator-teachers, deriving of three different areas of academic formation. The instruments of data collection consist of eight life histories, 32 contextualization applications of the participants of the research, interviews with two consultants of the project, as well as some documents. The results of the analyses put in evidence that the education of the educator-teacher goes for two parallel ways: the first deals with the experiences, interactions and elements of daily practice; the second with the academy experiences where the educator-teacher searches the post-graduation courses. The integration of these two ways defines the educator-teacher identity with foundation in knowings that constitute in the exercise of guidance of memorials. The teachers knowings are considered insufficient by the majority and others knowings are mobilized to the knowing to be educator-teacher, memorial tutor. The thesis concludes that the trajectory of the educator-teacher constitutes an educator experience, in the direction of that implies an articulation among the learnings, abilities and knowings, to support the pupil in self-discovery, and that these multiple experiences favor the education of these teachers